Nanonetwork photogrowth expansion: Tailoring nanoparticle networks' chemical structure and local topology. Issue 28 (1st July 2019) - Lampley, Michael W.; Tsogtgerel, Enkhjargal; Harth, Eva
Abstract : Parent nanoparticle networks containing trithiocarbonate photoactive groups form nanonetworks with incorporated homopolymers, random copolymers and block copolymers through a developed photogrowth expansion process. Abstract : The manipulation of covalent polymer networks in the bulk or in the nanoscale seeks to broaden material property variations from an existing parent structure with the possibility to make fundamental changes in nanoparticle compositions which is otherwise difficult to accomplish through bottom up approaches. In this contribution, a parent nanoparticle network prepared by an intermolecular chain cross-linking process containing trithiocarbonate photoactive cross-linking groups has been investigated in its ability to form various novel nanonetworks through a photogrowth expansion process using 10-phenylphenothiazine (PTH) as a photoredox catayst under violet light irradiation, incorporating statistical copolymers and block copolymers into the existing nanonetwork. Hydrophilic and hydrophobic homo-and statistical copolymer incorporation leads to custom designed, tailored nanonetworks and stimuli-responsive behavior. For example, particles expanded by incorporation of PNIPAAM collapse after thermoresponsive behavior above 32 °C and shrink to approximately half of their original size. Furthermore, ABA triblocks and ABABA pentablocks of MA, TFEA, NIPAAM and t BA are integrated with a high degree of control into a parent particle. In this work, we have demonstrated the feasibility of parent nanonetwork structures to expand their network architecture reaching up to the microscale range to give soluble soft matter networks, containing controlled compositions of homopolymers, statistical copolymers, or pentablock structures. The taught concept gives opportunities to further design and alter the network topology in confined structures to tailor properties and function.